Սիմվոլիզմի դրսևորումները Վարդգես Սուրենյանցի արվեստում - Մանե Մկրտչյան (ՀՀ ԳԱԱ հրատ.)
The main subject of the article is the influence of Symbolism on the art of the prominent Armenian artist Vardges Sureniants. Having graduated from Munich Academy of Fine Arts, Sureniants was familiar with modern tendencies in art which influenced his oeuvre.
Keywords: Biography; Fine Arts; Painting